The Effectiveness of Interventions Using Electronic Reminders to Improve Adherence to Hypertension Medication: A Systematic Review - Susanti, Ika Adelia; Efendi, Ferry; Pramono, Ahmad Putro; Habibie, Aziz Nashiruddin (International Journal of Psychosocial Rehabilitation, 2020)
Hypertension is a global health problem and a major risk factor for cardiovascular diseases such as ischemic heart disease and stroke. Increasing the prevalence of hypertension causes morbidity and premature mortality as well as rises the burden of health costs. One of the most important treatments is adherence to medication and lifestyle modification, but those interventions need to be enhanced. The study was aimed to evaluate the effectiveness of electronic reminders to improve adherence in patients with hypertension. This systematic review used the related elements to content chosen by the PRISMA statement. Four databases were used to collect the data, SCOPUS, PUBMED, CINAHL, and MEDLINE with articles published between 2010 and 2019. Only randomized control trials (RCTs) with hypertension patients without any acute complications and healthcare professionals have been collected on this study. The intervention was an electronic reminder to evaluate adherence and quality study should have been conducted. The primary outcomes were changes in mean systolic and diastolic blood pressure values and patients’ compliance. Fourteen articles were included to assess adherence and blood pressure as outcomes. The most effective types of intervention were short message services (SMS), nurse-led email reminders, portal-based assessment, and electronic pillbox. An education session was conducted in each intervention. Medication adherence and hypertension control were improved after 24 weeks with reminders twice a day. Although different interventions had a different effect on blood pressure and adherence, overall, an SMS method can potentially improve adherence to hypertension. The majority of studies reported beneficial approaches to low cost and safety.